Design of PolyMUMPS device for diabetes screening via acetone vapor detection in exhaled breath - Rabih, A.A.S. (American Institute of Physics Inc., 2016)
Diabetes is a chronic disease that occurs due to deficiency or improper use of insulin by body tissues. It is currently diagnosed invasively by measuring blood glucose. This paper reports modelling and simulation of a PolyMUMPS device proposed for a non-invasive screening of diabetes. The device is electromagnetically driven at its resonance frequency using Lorenz force, while the output is detected by capacitive means. The resonance frequency of the first mode was obtained by CoventorWare software and it was found to be 18.552 kHz compared to its modelled value of 17.211 kHz, within an error of 7.2 . Maximum displacement of 8.35 Î¼m and capacitance of 29.57 fF were obtained when the device was driven by applying 15 mA current and 50 mT magnetic field. Â© 2016 Author(s).